A Method of Constructing Mobile Ground Station Location System Based on Optimizing Algorithms - Gao, Saisai; Tao, Zhu; Huang, Ying (Journal of physics. Conference series, 2019)
Aiming at the problem that the satellite navigation and positioning system can not cover the whole area and that the positioning accuracy of the existing ground-based reinforcement system decreases with the increase of the distance between the target and the ground station, a method for optimizing the positioning system of mobile ground station based on whale optimization algorithm is proposed. Based on the mobile ground station, the method identifies the positioning target with the optimal whale individual and the mobile ground station with other whale individuals, realizes that the position of the ground station varies with the position of the target point, and ensures the high precision positioning of the target in area with weak signals or without satellite navigation and without the support of the enhanced system. The feasibility of this method is proved by MATLAB, which provides a new way of thinking for solving the problem of regional target location.